Lect2 Controls Inflammatory Monocytes to Constrain the Growth and Progression of Hepatocellular Carcinoma. Issue 1 (22nd December 2018) - L'Hermitte, Antoine; Pham, Sandrine; Cadoux, Mathilde; Couchy, Gabrielle; Caruso, Stefano; Anson, Marie; Crain‐Denoyelle, Anne‐Marie; Celton‐Morizur, Séverine; Yamagoe, Satoshi; Zucman‐Rossi, Jessica; Desdouets, Chantal; Couty, Jean‐Pierre
Abstract : Leukocyte cell‐derived chemotaxin‐2 (LECT2) was originally identified as a hepatocyte‐secreted chemokine‐like factor and a positive target of β‐catenin signaling. Here, we dissected out the mechanisms by which LECT2 modulates hepatocellular carcinoma (HCC) development using both HCC mouse models and human HCC samples. We have demonstrated that LECT2 exhibits dual abilities as it has profound repercussions on the tumor phenotype itself and the immune microenvironment. Its absence confers Ctnnb‐1‐mutated tumor hepatocytes a stronger ability to undergo epithelial to mesenchymal transition and fosters the accumulation of pejorative inflammatory monocytes harboring immunosuppressive properties and strong tumor‐promoting potential. Consistent with our HCC mouse model, a low level of LECT2 in human HCC is strongly associated with high tumor grade and the presence of inflammatory infiltrates, emphasizing the clinical value of LECT2 in human liver tumorigenesis. Conclusion: Our findings have demonstrated that LECT2 is a key player in liver tumorigenesis because its absence reshapes the tumor microenvironment and the tumor phenotype, revealing LECT2 as a promising immunotherapeutic option for HCC.